ITS in a changing climate-a savior tool or another vulnerable system? - Leviakangas, Pekka (2011)
This paper describes a typology of components present in intelligent transport systems (ITS), or a physical architecture components of ITS and points out what type of weather phenomena are particularly harmful for ITS. The EWENT project's second work package studied what are the frequencies of extreme weather in different parts of Europe and how these frequencies are about to change. The means of six different regional climate models are presented. When looking at climate model projections the overall pattern in Europe is clear: the climate is getting warmer with more heat waves and fewer winter phenomena. Precipitation seems to turn from snow to water ever more often, but the change is of course still very uncertain. Warming causes increased risks of thunder storms which are associated with increased probability of heat waves. If heat waves increase significantly, as seems to be the case especially in Mediterranean, also sand storms may become more frequent and severe since heat waves could loosen the soil. All air-lifted sub-systems and outdoor equipment, such as path-side systems, are in principle at risk. The more intelligence and control can be shifted to in-vehicle systems, the lighter will the public sector cost burden probably be, thinking of the mitigation costs. © 2011 by the Intelligent Transportation Society of America.